The equilibrium moisture content of low-density thermal insulating materials/Lengvų termoizoliacinių medžiagų nuostovusis drėgnis - Gnip, Ivan; Vėjelis, Sigitas; Keršulis, Vladislovas (Journal of Civil Engineering and Management, 2001)
Data about water vapour sorption by modern low-density thermal insulating materials are very scarce. The isothermal sorption of water vapour dependent on relative air humidity was investigated for rock and glass wool products in this paper as well as for expanded and extruded polystyrene slabs and cellulose fibre produced in Lithuania, Poland and Estonia. The moisture in these materials is bound by several ways, therefore it is not possibile to express the equilibrium moisture Wp dependency on relative air humidity ϕ by an exact analytical equation [1, 6]. These dependencies were expressed by a two-constant empiric equation (1) for interval ϕ from 0 to 0,97 based on BET equations [1, 7, 8]. The experimental data are given in Figs 1–9, statistical treatment of this data results are given in Tables 1–3. The two fields are typical for all isothermal sorption curves: 0<ϕ<0,8 moisture bound as adsorbate) and 0,8<ϕ<0,97 (capillary bound moisture). The hygroscopicity of investigated glass wool products is higher than for rock wool products and depends on their density. This value is very small for expanded polystyrene and is considerable for cellulose fibre. Lengvų termoizoliacinių medžiagų nuostovusis drėgnis Santrauka. Literatūrinių duomenų apie vandens garų sorbciją, šiuolaikinėse lengvose termoizoliacinėse medžiagose yra nedaug. Straipsnyje ištirtos akmens ir stiklo vatos gaminių, polistireninio putplasčio plokščių ir ekovatos sorbcijos izotermos priklausomybė nuo aplinkos oro santykinio drėgnio ϕ. Kadangi drėgmė šiose medžiagose sujungta keliais būdais, tiksli analizinė šios priklausomybės išraiška yra praktiškai neįmanoma [1, 6]. Todėl, remiantis BET lygtimis [1], ši priklausomybė ϕ intervalu nuo 0 iki 0,97 buvo išreikšta dvikonstante empirine lygtimi (1) [1, 7, 8]. Eksperimentiniai duomenys pateikti 1–9 pav., jų statistinio apdorojimo rezultatai – 1–3 lentelėse. Visoms sorbcijos izotermoms charakteringos dvi zonos: 0<ϕ<0,8 (absorbcinis drėgnis) ir 0,8<ϕ<0,97 (kapiliarinis drėgnis). Tyrinėtų stiklo vatos gaminių higroskopiškumas yra didesnis negu akmens vatos gaminių ir priklauso nuo gaminių tankio. Mažiausiai drėgmę iš aplinkos sorbuoja polistireninis putplastis, labiausiai – ekovata. Article in Russian.